Cognitive radio networks : medium access control for coexistence of wireless systems - Bian, Kaigui; Park, Jung-Min; Gao, Bo (Springer International Publishing, 2014)
This book gives a comprehensive overview of the medium access control (MAC) principles in cognitive radio networks, with a specific focus on how such MAC principles enable different wireless systems to coexist in the same spectrum band and carry out spectrum sharing.  From algorithm design to the latest developments in the standards and spectrum policy, readers will benefit from leading-edge knowledge of how cognitive radio systems coexist and share spectrum resources.  Coverage includes cognitive radio rendezvous, spectrum sharing, channel allocation, coexistence in TV white space, and coexistence of heterogeneous wireless systems.   • Provides a comprehensive reference on medium access control (MAC)-related problems in the design of cognitive radio systems and networks; • Includes detailed analysis of various coexistence problems related to medium access control in cognitive radio networks; • Reveals novel techniques for addressing the challenges of coexistence protocol design at a higher level of abstraction; • Discusses technical challenges of MAC layer protocol design for heterogeneous wireless systems as well as potential solutions.